2021
DOI: 10.1177/2041669520983338
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Eye Tracking Latencies Among Several Commercial Head-Mounted Displays

Abstract: A number of virtual reality head-mounted displays (HMDs) with integrated eye trackers have recently become commercially available. If their eye tracking latency is low and reliable enough for gaze-contingent rendering, this may open up many interesting opportunities for researchers. We measured eye tracking latencies for the Fove-0, the Varjo VR-1, and the High Tech Computer Corporation (HTC) Vive Pro Eye using simultaneous electrooculography measurements. We determined the time from the occurrence of an eye p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 70 publications
(71 reference statements)
0
36
0
Order By: Relevance
“…Thanks to the colour recognition subtask and the scotoma radii thresholding, the data were corrected for eye-tracking delays (25 ms). However, this end-to-end latency [31,32,44] is not stable as it can be seen in the results, and therefore may have influenced the scotoma positioning similarly to previous gazecontingent paradigms [44,45].…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Thanks to the colour recognition subtask and the scotoma radii thresholding, the data were corrected for eye-tracking delays (25 ms). However, this end-to-end latency [31,32,44] is not stable as it can be seen in the results, and therefore may have influenced the scotoma positioning similarly to previous gazecontingent paradigms [44,45].…”
Section: Discussionmentioning
confidence: 62%
“…In this study, the HTC Vive Pro Eye, which is known to have an end-to-end latency between 58.1 ms [31] and 80 ms [32] was used. Thanks to the colour recognition subtask and the scotoma radii thresholding, the data were corrected for eye-tracking delays (25 ms).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite leaps and bounds being made in HMD eye tracking technology(Clay et al, 2019), they are understandably inferior in terms of tech specifications to research-grade eye trackers. However, our choice of HMD for the VR framework eventually proved to be reasonable -Stein et al (2021) showed that the FOVE had the lowest latency among a group of HMDs with built-in eye tracking.…”
mentioning
confidence: 98%
“…Therefore, several studies have been performed to evaluate the performance of commercial eye tracking systems in different operating environments. For a detailed review about the methods for performance evaluation of eye tracking and technical characteristics of commercially available eye trackers, refer to the studies performed by Zhang et al [146], Cognolato et al [135], Lim et al [142], and Stein et al [147]. Data quality refers to the reliability, validity, and availability of the eye tracking data.…”
Section: Eye Tracker Performance and Data Qualitymentioning
confidence: 99%